2007
DOI: 10.1152/ajpendo.00685.2006
|View full text |Cite
|
Sign up to set email alerts
|

Two phases of palmitate-induced insulin resistance in skeletal muscle: impaired GLUT4 translocation is followed by a reduced GLUT4 intrinsic activity

Abstract: Alkhateeb H, Chabowski A, Glatz JF, Luiken JF, Bonen A. Two phases of palmitate-induced insulin resistance in skeletal muscle: impaired GLUT4 translocation is followed by a reduced GLUT4 intrinsic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 68 publications
9
98
0
2
Order By: Relevance
“…However, the decreased ability of insulin to phosphorylate Akt on T308 and induce GLUT4 translocation did not result in reduced glucose uptake, which suspected the exclusive role of GLUT4 translocation in glucose uptake (Tajmir et al, 2003). In particular, a reduction of intrinsic GLUT4 activity has been suggested to be a contributor to insulin resistance in obese diabetic subjects (Alkhateeb et al, 2007). In L6 muscle cells, insulin-stimulated glucose transport was reduced by altering the intrinsic activity of cell surface GLUT4 without change of GLUT4 translocation and Akt phosphorylation (Moon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the decreased ability of insulin to phosphorylate Akt on T308 and induce GLUT4 translocation did not result in reduced glucose uptake, which suspected the exclusive role of GLUT4 translocation in glucose uptake (Tajmir et al, 2003). In particular, a reduction of intrinsic GLUT4 activity has been suggested to be a contributor to insulin resistance in obese diabetic subjects (Alkhateeb et al, 2007). In L6 muscle cells, insulin-stimulated glucose transport was reduced by altering the intrinsic activity of cell surface GLUT4 without change of GLUT4 translocation and Akt phosphorylation (Moon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-stimulated glucose uptake was achieved by activating only 10-20% of insulin receptor substrate-1 (IRS-1) and Akt in one study (Whitehead et al, 2001), and insulinstimulated Akt activation was not severely impaired in obese individuals with insulin resistance in another study (Storgaard et al, 2004), indicating that factors other than an impaired insulin signaling pathway may be involved in the induction of insulin resistance. Additionally, a report that palmitate induces insulin resistance without a defect in insulin-stimulated Akt phosphorylation in the soleus muscle (Alkhateeb et al, 2007) suspects a role for impairment of the insulin signaling pathway in PIIR. In particular, Cleasby et al reported that reduced IRS-1 levels in muscle did not severely impair insulin action (Cleasby et al, 2007) and Hoehn et al revealed that upstream elements of the insulin signaling cascade are not a central feature of the origin of insulin resistance (Hoehn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramuscular lipids Control and transfected muscles were analysed for triacylglycerol, diacylglycerol and ceramide content as reported previously [22,23]. Briefly, lipids were extracted with a modified Folch procedure and thin-layer chromatography was used to separate lipids.…”
Section: Intramuscular Lipids and Mitochondrial Fatty Acid Oxidationmentioning
confidence: 99%
“…Intramuscular levels of triacylglycerol, diacylglycerol and ceramide were measured as described previously [21].…”
Section: Biochemical Determination Of Intramuscular Lipid Contentmentioning
confidence: 99%